Spirituality, quality of life, and depression in older people with dementia - Agli, Océane (Journal of religion, spirituality & aging, 2018)
This study aimed to observe dementia's role in the relationship between spirituality, quality of life, and depression in aging. The sample included 61 participants between 65 and 98 years old, separated into two groups: participants diagnosed with dementia (N = 31) and control participants (N = 30). There was no significant difference in spirituality between demented and control participants; however, different patterns of correlation were observed between spirituality, depression, and quality of life in these groups. Although the level of spirituality did not differ despite dementia, this pathology would appear to play a role in the relationship between spirituality, quality of life, and depression.